ANALISIS STRATEGI PENCAPAIAN TARGET PENJUALAN RENGGINANG UD WARNA WARNI BANJARMASIN - Rika Sylvia; Ni Nyoman Suarniki; Dwiki Cahayanti (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, The purpose of this study was to determine the strategies that must be carried out to achieve the target of the sales of the rengginang UD Warna Warni Banjarmasin. This type of research is a descriptive qualitative research subjects in this study amounted to 10 respondents. Data analysis technique used is to use SWOT analysis, namely by describing the internal environment and external environment which are strengths, weaknesses, opportunities and threats of UD Warna Warna Banjarmasin business. Based on the results of research from the internal side, the strength of rengginang UD Warna Warni Banjarmasin is greater than its weakness, the IFAS calculation results are 3.06 with the difference between strengths and weaknesses having a positive value of 0.27. While externally the opportunity is smaller than the threat, the EFAS calculation point is 2.97 with the difference between the opportunity and the threat has a negative value of -0.015. From the results of the SWOT calculation show that the business of UD Warna Warni Banjarmasin in quadrant II position, which indicates facing various threats, this company still has strengths from an internal perspective. The strategy that must be applied is to use power to take advantage of long-term opportunities by means of a product diversification strategy.